Impacts of ocean warming on a reef-building coralline alga Amphiroa cf. fragilissima under high irradiance - Yang, Fangfang; Wei, Zhangliang; Long, Lijuan (Frontiers in Marine Science, 2022)
Coralline algae, an important calcifying group, play vital roles in the primary productivity, reef frameworks construction, and carbon store. In this study, we investigated the responses of an articulated coralline alga Amphiroa cf. fragilissima to ocean warming under various light intensities. The relative growth rate significantly decreased under light or heat stress. When A. cf. fragilissima was exposed to high light intensity (120 μmol photons m−2 s−1) at 32°C, the relative growth rate was lowest, which reduced by 87% compared with that of group A1 (60 μmol photons m−2 s−1, 26°C). Meanwhile, a higher level of algal bleaching occurred when light intensity was 120 μmol photons m−2 s−1. Similarly, Fv/Fm and Chl-a content were negatively affected by light and heat stress, but they were more affected by light. Furthermore, the mineralogical responses to temperature and light were investigated. The net calcification rate declined from 92.27 (60 μmol photons m−2 s−1, 26°C) to 10.92 μmol CaCO3 g−1 DW day−1 (120 μmol photons m−2 s−1, 32°C). High temperature significantly decreased Ca content in live algal pigmented layer, whereas there were no significant differences in Ca content in the skeleton layer, implying that the pigmented layer could protect skeleton layer from mineral changes under ocean warming. The results revealed that A. cf. fragilissima was impaired by high light or thermal stress from various aspects, including growth, survival, photosynthesis, reproduction, and calcification. This study contributes to understand the effects of warming and light on coralline algae and provides a theoretical basis to protect the richness and diversity of calcified macroalgae.